32. Risk Factors for Vertical Transmission of t. Cruzi infection in an Endemic Setting. (31st December 2020) - Klein, Melissa D; Tinajeros, Freddy; Malaga, Edith; Verástegui, Manuela; Condori, Beth J; Urquizu, Federico; Gilman, Robert; Bowman, Natalie M
Abstract: Members of the Chagas Disease Working Group in Peru and Bolivia include: Edith Hinojosa, Clariza Chavez, Jean Karla Velarde, Carla Chavarria, Victoria Serrudo, Roberto Araya, Alcides Buitron, Rita Mendieta, Holger Mayta, Maritza Calderon, Holger Mayta and Yagahira Castro. Background: Vertical transmission of Trypanosoma cruzi infection accounts for a growing proportion of new cases of Chagas disease. Congenital infection is curable if treated promptly, but the majority of infected infants do not receive timely diagnosis or treatment. Better risk stratification is needed to predict which women are more likely to transmit the infection. Methods: This study enrolled women who presented for delivery and their infants at the Percy Boland Women's Hospital in Santa Cruz, Bolivia. Pregnant women were screened for Chagas disease by rapid test. The infants of seropositive mothers underwent diagnostic testing with microscopy ("micromethod") and quantitative polymerase chain reaction (qPCR) as newborns and at one- and nine-month follow-up. Mothers completed surveys about demographics and medical history. Results: Among 5, 828 enrolled women, 1, 271 (21.8%) screened positive for Chagas disease. Of the 1, 325 infants of seropositive mothers, 113 (8.5%) were diagnosed with congenital Chagas disease by microscopy or qPCR. Cesarean delivery was significantly associated with lower odds of vertical transmission (adjusted OR: 0.63, 95% CI: 0.41–0.98, p=0.040). Congenital infection was more common in twins (adjusted OR: 3.30, 95% CI: 1.97–5.54, p< 0.001) and male infants (adjusted OR: 1.50, 95% CI: 1.01–1.22, p=0.045). Conclusion: Our findings suggest that Cesarean delivery may be protective against vertical transmission of T. cruzi, while twins and male infants may have an increased risk. A better understanding of risk stratification for congenital Chagas disease may help improve regional initiatives to reduce disease burden. Disclosures: All Authors : No reported disclosures